Utilization of Digital Media in Kitabah Learning: Efforts to Increase Creativity and Writing Productivity - Arifani, Ahmad Zainul; Maulana, Akbar; Tanjung, Anas Kholil; Imran, Muhammad Ali (Holistic Science, 2025)
Due to rigid teaching methods that are not relevant to everyday communication situations, students often find learning to write in Arabic difficult. Using digital media as a learning aid is one solution to overcome this problem. The purpose of this study was to see how the use of digital media such as Google Docs, Canva, and Padlet can improve students' creativity and writing productivity when learning Arabic. This bibliometric research approach analyzed various relevant literature sources, including textbooks, Arabic language education journals, and scientific articles that discuss the use of technology in learning Arabic. The results showed that the use of online applications and original texts from the internet improved students' writing skills. In addition, digital media makes learning more interactive and fun. This makes students' understanding of sentence structures and expressions used in the real world easier. Therefore, the Arabic language curriculum should adopt a digital media-based learning approach as an effort to create more modern, engaging, and contextual learning. This method not only improves students' writing skills but also increases their desire to learn Arabic.